Analysis of knowledge, perceptions and self-confidence regarding tobacco control among graduating nursing students in Portugal - Afreixo, Vera (2019)
In the 20th century, the tobacco epidemic killed around 100 million people worldwide, and in the present century can be the cause of billions of deaths. WHO advocates that the solution to this global epidemic, which is a risk factor for six of the eight leading causes of death in the world, is within our reach. The Government of Portugal signed the Framework Convention of the World Health Organization for Tobacco Control on January 9th, 2004, approving it and transposing it into national law on November 8th, 2005. The National Health Plan 2012-2016 considered smoking a priority health problem, and in 2012 it was created the National Program for Smoking Prevention and Control, a priority health program developed by the Director General of Health (DGS). With reference to this framework, the DGS launched a public tender for the study of evaluation of the acquisition of professional skills in the field of prevention and treatment of smoking during the nursing degree’s final year. This study aims to explore attitudes, knowledge, perceptions of curricula contents and confidence to intervene in tobacco control among graduating nursing students in Portugal.